The Concentration of Citric Acid Affects the Properties of Peking Duck (Anas platyrhynchos domestica) Bone Gelatin - Saputra, Antony; Afifah, Ika Qurrotul (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
Cows and pigs are the major contributors to the production of gelatin, but ethical, religious, environmental, and health concerns are prompting the exploration of gelatin sources from other materials. In the study, gelatin has been isolated from the bones of Peking duck (Anas platyrhynchos domestica) by altering the citric acid concentration in the pre-treatment process. This study aims to identify gelatin functional groups present in products derived from Peking duck bones and to assess the effect of citric acid concentration on the properties of the isolated gelatin. The pre-treatment process was conducted by soaking in 11, 13, and 15% citric acid for 72 h. Distilled water was used to extract gelatin in a water bath at gradual temperatures of 50, 65, and 80 °C for 4 h. The gelatin extract was then dried using an oven for 72 h. Gelatin characterization involves determining functional groups, calculating yield, pH, water content, ash content, and protein content. Functional group analysis using (FTIR) spectrophotometer revealed that the product has gelatin typical absorption properties, including Amide A, Amide I, Amide II, and Amide III. Citric acid concentrations can have a significant impact on yield, pH, water content, ash content, and protein content. The optimal concentration for producing gelatin is 15%, resulting in a yield of 11.89%, pH 4.085, water content 4.60%, ash content 10.48%, and protein content 58.31%. The ash content was above 3.25%, which was not in compliance with Indonesian National Standard (SNI), but the pH and water content values were in line with Gelatin Manufacturers Institute of America (GMIA) and SNI standards. Therefore, further optimisation of the soaking time is necessary.